Analisa Efisiensi Belajar Menggunakan Beberapa Jenis Lampu - Rizqi, Fathir; , Ir. Jatmiko, M.T (2017)
Learning is the obligation for students, a lot of things or aspects that influence whether or not optimal learning. One important aspect which affects the lighting or illumination is, if the light is dimmed in classrooms make the vision in the eye can be gradually reduced and sleepy, if the lights are too bright, it can make learning concentration is reduced and make easy eye fatigue. The standard of lighting in the room is a study of 240 Lux. Analysis of the efficiency study carried out in two ways: in a room with a length of 3m and 3m wide (3x3) and use the light of learning to the distance between the lamp with a book or a work area of 45cm. Analysis of this lighting can be analyzed or measured by using a Lux meter and manual calculations. The analysis aims to determine the type, wattage and lamp brand which is the most efficient way to learn. The method used is dimuali of collecting data and information, purchase materials, conduct measurements using light Lux Lux Meter, perform manual calculations, making comparisons and conclusions. The conclusion of this study is based on analysis of efficiency there are two kinds of the room and use the light of learning. Results of analysis of the most effective learning in a room with a length of 3m and 3m wide (3x3) is to use the type of lamp LHE 20 Watt with Philips brand that is equal to 46 Lux, while analysis of the most effective uses lamp learn is to use the type of fluorescent lamp 10 Watt the Philips brand is equal to 241 Lux. Keywords: analysis, lamp, lux meter, study, efficient